2021
DOI: 10.1111/all.15089
|View full text |Cite
|
Sign up to set email alerts
|

Advances and highlights in biomarkers of allergic diseases

Abstract: During the past years, there has been a global outbreak of allergic diseases, presenting a considerable medical and socioeconomical burden. A large fraction of allergic diseases is characterized by a type 2 immune response involving Th2 cells, type 2 innate lymphoid cells, eosinophils, mast cells, and M2 macrophages. Biomarkers are valuable parameters for precision medicine as they provide information on the disease endotypes, clusters, precision diagnoses, identification of therapeutic targets, and monitoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(76 citation statements)
references
References 224 publications
(585 reference statements)
0
51
0
1
Order By: Relevance
“…Atopic dermatitis (also known as atopic eczema), food allergies, asthma, and allergic rhinitis are the most common allergy-related diseases with similar epigenetic and physiopathological characteristics [ 22 , 23 ]. Numerous experimental and clinical studies have shown that the poor prognosis of atopic dermatitis and food allergies in early life greatly exacerbates the occurrence of later asthma and allergic rhinitis [ 1 4 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Atopic dermatitis (also known as atopic eczema), food allergies, asthma, and allergic rhinitis are the most common allergy-related diseases with similar epigenetic and physiopathological characteristics [ 22 , 23 ]. Numerous experimental and clinical studies have shown that the poor prognosis of atopic dermatitis and food allergies in early life greatly exacerbates the occurrence of later asthma and allergic rhinitis [ 1 4 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A review by Breiteneder et al found that some of them achieved a better classification of distinct phenotypes or endotypes and increased the necessity to use biomarkers for patient selection, prediction of results and monitoring [ 13 ]. Ogulur et al [ 14 ] stated that such biomarkers are valuable parameters as they make information on the disease endotypes, clusters, identification of treatment targets and monitoring of efficacy available. These powerful omics technologies, together with integrated data analysis, are useful in identifying clinical biomarkers; these, however, need to be precisely measured by solid and reproducible methods.…”
Section: Omicsmentioning
confidence: 99%
“…The search for novel biomarkers of allergic diseases resulted in promising biomarkers of type-2 allergic diseases, including sputum eosinophils, exhaled nitric oxide and serum periostin. Biomarkers such as pro-inflammatory mediators, eicosanoid molecules, epithelial barrier integrity and microbiota changes quantified in serum, exhaled air and body fluids are suitable for diagnosing and monitoring allergies and, particularly, the efficacy of AIT, also considering the perspective of the COVID-19 pandemic [ 14 ].…”
Section: Omicsmentioning
confidence: 99%
“…Its direct role on epithelial cells and barrier function has yet to be described. TSLP blockers (Tezepelumab) could then represent an interesting option for future treatments [ 76 ].…”
Section: Type 2 Inflammatory Cytokines and Tslpmentioning
confidence: 99%